Particularistic and system trust among small and medium enterprises: A comparative study in China's transition economy - Tan, Justin; Yang, Jun; Veliyath, Rajaram (Journal of Business Venturing, 2009)
Guanxi, a type of particularistic trust observed in Confucian societies has mostly been viewed as a static phenomenon. It is not clear how the role of guanxi changes over time during institutional transitions. This field study of twenty one small and medium enterprises (SMEs) located in two large cities in Western China examines the changes in SME behaviors since the beginning of economic reforms in 1979. Based on neo-institutionalist trust perspectives, the article argues that the role of guanxi also arose from the paucity of market system trust created by the absence of well-established market institutions during China's transition from a centrally planned to a market economy. Guanxi became relatively less important when market system trust based on well-established institutions was firmly established. Regardless of past practices, the dynamics of institutional transitions leading to the establishment of system trust inevitably reshapes managerial as well as business behaviors, with adaptation occurring to the new rules of the market economy.